(3aGYdjI HQfGeL GQTGOi ddCegGJ ddMO ef GdGVWQGH GdeTJQc dOi GWaGdgf Phi UYhHGJ GdJYde (B/s - (3,SYjOI aQL EHQGgje SjO CMeOs; (3NGdO YHO GdQGRb GdfLGQs; (3gHI ESeGYjd eJhdjs (2025)
(3gOa GdHMK GdMGdj Edi NaV GdGVWQGH GdeTJQc dOi GdCWaGd Phj oUoYhHGJ GdnqJYoqde hPdc ef NdGd HQfGeL ErQTGpOqj ddCnqegGJ(B. (3Je GSJNOGe GdefgL THg GdJLQjHj(B. (3JchfJ Yjfg GdHMK ef (B(10) (3CWaGd ef GdCWaGd Phj oUoYhHGJ GdnqJYoqde GdPjf JQGhMJ CYeGQge ef (B(5- 6) (3SfhGJ eY CnqegGJge heYdeGJge(B. (3GTJedJ COhGJ GdHMK Ydi GNJHGQ GdeUahaGJ GdeJJGHYI Gdedhf dbjGS GdPcGA JCdja Lhf QGaf JYOjd hJbfjf YeGO CMeO MSf, (B2016)(3, hHWGQjI JTNjU oUoYhHGJ GdnqJYoqde GdfeGFjI (B((3EYOGO aJMj GdRjGJ, (B2008)(3, hebjGS GdGVWQGH GdeTJQc UhQI GdCe hUhQI GdWad hUhQI GdeYdeI ddCWaGd Phj oUoYhHGJ GdnqJYoqde (B((3EYOGO GdHGMKI(B). (3hbO CSaQJ GdfJGFL Yf aGpYpdnqjI GdHQfGeL GdErQTGpOqj ddCnqegGJ aj NaV MOI GdGVWQGH GdeTJQc dOi CWaGdgf Phj oUoYhHGJ GdnqJYoqde(B.s
The current research aimed to reduce the shared disorder in children with learning disabilities through a guidance program for mothers. The quasi-experimental approach was used. The research sample consisted of 10 children with learning disabilities whose ages ranged from (5-6) years with their mothers and teachers. The research tools included the Colored Progressive Matrices Test to measure intelligence (authored by John Raven, modified and standardized by Imad Ahmed Hassan, 2016), the Developmental Learning disabilities Diagnosis Battery (prepared by Fathi Al-Zayat, 2008), and the shared Disorder Scale (Mother Image, Child Image, and Teacher Image) for children with learning difficulties (prepared by the researcher). The results showed the effectiveness of the guidance program for mothers in reducing the severity of the shared disorder in their children with learning disabilities
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2025. s
(3HHdjhLQGajG(B: (3UaMGJ (B159-169.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdJYdje GdNGUs; (3HQfGeL ErQTGpOqj ddCnqegGJ s -- (3GdGVWQGH GdeTJQcs -- (3GdCWaGd Phj oUoYhHGJ GdnqJYoqdes